Boosting the power conversion efficiency of perovskite solar cells based on Sn doped TiO2 electron extraction layer via modification the TiO2 phase junction. (15th July 2020) - Liao, Ying-Han; Chang, Yin-Hsuan; Lin, Ting-Han; Chan, Shun-Hsiang; Lee, Kun-Mu; Hsu, Kai-Hsiang; Hsu, Jen-Fu; Wu, Ming-Chung
Graphical abstract: Highlights: Doping Sn can facilitate the formation of anatase/rutile phase junction. The TiO2 phase junction can decrease the bandgap and promote the charge carrier mobility. Sn/TiO2 electron extraction layer can reduce the trap-assisted recombination. The PCE of perovskite solar cell based on 1.0 mol% Sn/TiO2 electron extraction layer can be achieved to 15.4%. Abstract: Perovskite solar cells (PSCs) have earned considerable attention and are candidates against the inevitable energy crisis. Even though various successful PSCs have emerged, increasing the PCE by reinforcing charge collection is still a critical issue. The manipulation of carriers between the perovskite active layer and the electron extraction layer (EEL) is essential. Here, we prepared a tin-doped TiO2 (Sn/TiO2 ) EEL that presented two main polymorphs, anatase and rutile, and successfully fabricated a high-performance planar PSCs. Besides, the band alignment between EEL and perovskite active layer could be optimized by tuning the Sn doping concentration and the ratio of anatase and rutile phases. The intrinsic conductivity, interface morphology, band alignment, and charge carrier dynamic were characterized and the relationship to the photovoltaic performance was clarified. As the Sn ions being doped into TiO2 structure, EEL presented the mixed TiO2 rutile/anatase phase, directly narrowing the bandgap and promoting mobility. Furthermore, the adjustment of the band structure can facilitate electronic transitions. Finally, a promising planar PSC with Sn/TiO2 phase junction EEL achieved a champion PCE of 15.4%.